Alberto Flores Galindo, left –wing intelectual - Gonzales Alvarado, Osmar (2020)
This essay is located temporally in the post oligarchic Peru, in the 70’s, especially in the politic and intellectual scenario that was the result of a new period. In this context took place the renewal of some ideas, it was established for a generation of left –wing young intellectuals engaged in creating and shaping a new society. They got a combination of a deep theoretical reflection and a political action that would significantly renewed social sciences and history. In this new generation of intellectuals would be recognized and well known, Alberto Flores Galindo, as an intellectual, historian and most important ideologist